Association between Consumption Habits of Packaged Sugar-Sweetened Beverages and the Risk of Type 2 Diabetes Melitus among Medical Students at the University of Jambi, Class of 2025, in 2026 - Zahra Suci Ramadhani; Yulinda Fetritura; Lipinwati .; Erny Kusdiyah; Hafizah . (CV. ITTC INDONESIA, 2026)
Background: Type 2 Diabetes Mellitus (DMT2) is one of the non-communicable diseases whose prevalence continues to increase globally. This increase in prevalence is mainly due to lifestyle changes, such as unhealthy diets and lack of physical activity. One of the main risk factors that contribute to the increased incidence of DMT2 is the consumption of sweetened beverages. The purpose of this study is to find out how the consumption habits of Packaged Sweetened Beverages are related to the Risk of Type 2 Diabetes Mellitus Among Medical Study Program Students of the University of Jambi Class of 2025 in 2026. Methods: This study uses a quantitative method with a cross-sectional design to determine the relationship between the consumption of packaged sweetened beverages and the risk of Type 2 Diabetes Mellitus Among Medical students of the University of Jambi Class of 2025 in 2026. The research was carried out in February-March 2026 using a total sampling of 139 students. Data were collected through SQ-FFQ QUESTIONNAIRES, GPAQ, BMI MEASUREMENTS, AND BLOOD SUGAR CHECKS WHILE USING GLUCOMETERS. Data analysis was carried out univariate and bivariate using the Chi-Square test with a significance level of 0.05 and still paying attention to the principles of research ethics through informed consent and confidentiality of respondent data. Results: This study used an analytical observational design with a cross-sectional approach on 116 students of the 2025 Batch of Medicine Study Program, FKIK, University of Jambi. The majority of respondents were 19 years old (47.4%), female (69.18%), had normal BMI (71.6%), normal blood sugar levels (GDS) (87.9%), low consumption of sweetened beverages (87.9%), and moderate physical activity (66.4%). The results of the Pearson Chi-Square analysis showed a significant association between the consumption of packaged sweetened beverages and the risk of type 2 diabetes mellitus (p < 0.001). Most respondents with normal GDS had a low consumption rate of sweetened beverages (99%), while the majority of abnormal respondents (92.9%) were in the moderate consumption category. These findings suggest that higher consumption of sweetened beverages is associated with an increased risk of type 2 diabetes mellitus. Conclusion: The majority of respondents had low consumption of packaged sweetened beverages (MBDK) and normal blood sugar levels. The results of the Pearson Chi-Square test showed a significant association between MBDK consumption and the risk of type 2 diabetes mellitus (p < 0.001), where higher consumption was likely to be associated with abnormal conditions.